2021
DOI: 10.1115/1.4049599
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Intelligence Optimization Algorithms in the Thermo-Economic Performance of an Energy Recovery System Based on Organic Rankine Cycle

Abstract: This paper compares the performance of a group of intelligent algorithms such as the genetic algorithm (GA), particle swarm optimization (PSO), and repulsive particle swarm optimization (RPSO) based on the optimization of thermo-economic indicators such as the payback period (PBP), the levelized energy cost (LEC), the specific investment cost (SIC), and also in the optimization of the thermodynamic process (net power output) of an energy recovery system in a 2 MW natural gas internal combustion engine based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In this work, the authors minimized the environmental impact by maximizing energy and exergy indicators. Other works have focused on the study of different optimization algorithms as reported by Duarte et al [ 31 ]. In this study, the authors evaluated the performance of three optimization algorithms (PSO, RPSO, and GA) using an organic Rankine cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the authors minimized the environmental impact by maximizing energy and exergy indicators. Other works have focused on the study of different optimization algorithms as reported by Duarte et al [ 31 ]. In this study, the authors evaluated the performance of three optimization algorithms (PSO, RPSO, and GA) using an organic Rankine cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Based on machine learning, the GA and PSO were combined into a GA-PSO hybrid algorithm to predict and optimize the pump isentropic efficiency under full operating conditions in an ORC system [24]. The performances of GA, PSO, and repulsive particle swarm optimization (RPSO) based on the optimization of thermo-economic indicators were compared as well as in the optimization of the thermodynamic process of an ORC energy recovery system [25]. A multi-objective optimization using the PSO algorithm aimed at the proposed heat exchanger was conducted and the optimal design scheme had the potential to achieve a 71.46% decrease in the total annual cost [26].…”
Section: Introductionmentioning
confidence: 99%